Plasma‐Activated Polypropylene Mesh‐Gelatin Scaffold Composite as Potential Implant for Bioactive Hernia Treatment. Issue 3 (17th November 2014) - Gorgieva, Selestina; Modic, Martina; Dovgan, Barbara; Kaisersberger‐Vincek, Maja; Kokol, Vanja
Abstract: Novel, polypropylene mesh (PPmesh ) – gelatin scaffold (GELscaffold ) composites are prepared from O2 ‐plasma activated PPmesh, coated with GEL solution being in‐situ structured in a 3D scaffold with by‐preparation tuned, gradual porosity. The fabricated biomimetic‐like composites demonstrate frequency‐dependent rheological behaviour and high (up to 100%) intrinsic and/or by ϵ‐poly‐L ‐lysine evoked antibacterial activity against S. aureus and E. coli, latter demonstrating preparation‐dependant releasing profile, without triggering in‐vitro cytotoxicity. Finally, long‐term (up to 2 months) biodegradation resistance highlight the composite potential as active, biomimetic barrier in hernia treatment. Abstract : Potential of novel, PP mesh ‐GEL scaffold composites for active hernia treatment is demonstrated by means of extracellular matrix‐like gradual µ‐porosity, high elasticity, excellent intrinsic/ by ϵ‐poly‐L ‐lysine‐evoked antibacterial activity against S. aureus and E. coli, for 60% diminished fibrinogen adsorption, up to 2 months biodegradation resistance, and non cytotoxicity towards human ASC cells.